Ribes alpinum L. as a unique introduced material for breeding in Russia - Sorokopudov Vladimir (EDP Sciences, 2021)
Ribes alpinum L. has all useful properties (optimal combination of vitamins, sugars, organic acids, pectins) and, due to this, it deserves to be introduced into the breeding process. It was found that, in the conditions of the Belgorod region, Alpine currant develops normally and passes all phenological phases. The long-term variation in the timing of the phase onset is 25 days on the average. The studied forms of Ribes alpinum L. belong to phenologically early plants. In the cultivation for decorative purposes in the conditions of the Belgorod region, 5 forms are identified: large-fruited, compact, erect, erect dissected-leaved and spreading. There are 8 Alpine currant varieties (Evrika, Vorskla, Mulatka, Theodor, Dunyasha, Uslada, Krasnyi Schar, Zara) with a complex of economically valuable characteristics.